LEGAL IMPLICATION OF THE AUDIT BOARD OF INDONESIA ON MANAGEMENT AUDIT AND FINANCIAL LIABILITY OF THE STATE AGAINST STATE-OWNED ENTERPRISES - Henny Juliani (Diponegoro Law Review, 2018)
The objectives of tis research is to find out implication of BPK (Auditor Board of Republic of Indonesia) in the implementation of auditing and responsibility of state finance which is manage by state own company as regulated by national regulations. This study used normative juridical and analytic descriptive approach. The study indicated that BPK has authorities to conduct finance  audit and control and ask responsibility to BUMN management board because assets of BUMN is belonged to state assest although the assests is separated, it cannot be converted to be BUMN assest. Its juridical implication, there is not transformation from state finance to private finance in managing separated state assests, consequently BPK as independent external auditor has authority  to audit professionally.